2014
DOI: 10.32734/jpi.v3i1.2744
|View full text |Cite
|
Sign up to set email alerts
|

Hubungan Profil Peternak Dengan Pendapatan Usaha Ternak Kerbau Lumpur Di Kecamatan Lintong Nihuta Kabupaten Humbang Hasundutan

Abstract: Penelitian ini dilaksanakan di Kecamatan Lintong Nihuta, Kabupaten Humbang Hasundutan, PropinsiSumatera Utara yang dimulai tanggal Juli sampai Agustus 2012. Tujuan penelitian ini adalah untukmenganalisis pengaruh profil peternak terhadap pendapatan dalam ternak kerbau di kecamatan Lintong NihutaKabupaten Humbang Hasundutan. Metode penelitian yang digunakan adalah metode survey dengan unitresponden keluarga yang memelihara ternak kerbau. Metode penarikan sampel yang digunakan adalahProportional Stratified Rando… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Meanwhile, the 25-54 age group is the productive age group who already have family (married), and thus they had responsibilities to gain income for their family life; and then choose to raise buffalo. Makatita (2021) stated that age has no effect on a person's behavior, but Lumbantoruan et al (2014) highlighted that the farmer's age has a positive effect on the farmer's income. Moreover, a person's learning ability decreases after the age of 55-60 years, which affects his productivity (Padmowihardjo 1978).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Meanwhile, the 25-54 age group is the productive age group who already have family (married), and thus they had responsibilities to gain income for their family life; and then choose to raise buffalo. Makatita (2021) stated that age has no effect on a person's behavior, but Lumbantoruan et al (2014) highlighted that the farmer's age has a positive effect on the farmer's income. Moreover, a person's learning ability decreases after the age of 55-60 years, which affects his productivity (Padmowihardjo 1978).…”
Section: Resultsmentioning
confidence: 99%
“…The level of education influences a person's ability to manage a business (Riyanti 2003), maintain its sustainability, and overcome problems encountered (Alma 2010). The results of Lumbantoruan et al (2014) showed that education length affects the farmers' income. Makatita (2021) stated that the education level of the farmer had an effect (P<0.05) on their behavior.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation